苏轼诗词中菊花的意象 = The chrysanthemum imagery in Su Shi's poetry - 张欣颖 Chong, Sin Ying (2012)
菊花作为四君子之一，无论在文学、绘画、民俗上等等都具有特定的审美价值。东晋陶渊明以赋予菊花追求个体自由及生命价值的精神思想闻名，而宋代士大夫对陶潜人格修养及隐逸形象的推崇使宋朝成为咏菊的高峰时期。苏轼作为北宋的文学家、政治家及哲学家，其作品具有深远的影响。苏轼以菊写政治，借菊花的生长特性类比自身的政治生涯。诗人描写菊花重阳民俗意象的同时，加入了重阳典故的描绘。写重阳菊伤秋情绪之余，苏轼懂得适当调适自己的心境，此乃诗人在逆境中的生存法则。苏轼以其个人独特的审美视角刻画他眼中的菊，进而通过菊花耐寒及霜下杰的高尚品格写自身的人格修养。因此，菊花就像是苏轼的人格化身.Chrysanthemum as literary one of four gentleman, whether in literature, painting, folk has a specific aesthetic value. Tao Yuan Ming who is from Eastern Jin Dynasty (317-420) is known as to give chrysanthemum the pursuit of individual freedom and the spirit of the value of life. Song dynasty was the peak period of literary chrysanthemum description caused by the admired of Tao Yuan Ming’s personal accomplishment and seclusion image by Song scholar. And Su Shi as the Northern Song Dynasty writer, political and philosopher, his works has a profound impact. Different from others, Su Shi add on allusion while writing chrysanthemum Chung Yeung folk. While writing the autumn emotions of chrysanthemum, the poet know how to adjust his state of mind properly. This is how Su Shi faced the difficulty. Besides, chrysanthemum was a political metaphor because he described the growth characteristics of chrysanthemum as an analogy to his own political career. Su Shi wrote chrysanthemum with his own unique aesthetic perspective. He wrote chrysanthemum’s noble character as his own personal self-cultivation. Hence, chrysanthemum is the incarnation of Su Shi’s personality. Despite the chrysanthemum have faded, the flowers will never dying but still emitting a delicate fragrance.